2006
DOI: 10.1017/s0265021506000408
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative anxiety and postoperative behavioural disturbances in children

Abstract: Addition of subhypnotic dose of propofol to sevoflurane induction did not reduce the incidence of postoperative behavioural disturbances.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 16 publications
1
13
0
Order By: Relevance
“…Similar to ours, a study from Turkey reported no relation between the families' preoperative state anxiety level and their children's anxiety upon arrival to the operating room, at induction, and at the 13 th minute in the recovery room [17]. Previous studies in the 1990s from the United States [18,19] reported that a child's anxiety is strongly affected by the state-and trait-anxiety of the parent.…”
Section: Discussionsupporting
confidence: 84%
“…Similar to ours, a study from Turkey reported no relation between the families' preoperative state anxiety level and their children's anxiety upon arrival to the operating room, at induction, and at the 13 th minute in the recovery room [17]. Previous studies in the 1990s from the United States [18,19] reported that a child's anxiety is strongly affected by the state-and trait-anxiety of the parent.…”
Section: Discussionsupporting
confidence: 84%
“…18,28,29 Induction of anaesthesia may be the most stressful procedure a child experiences during his hospitalisation. 18,22,30,31 Inhalational anaesthesia is thought to be more suitable for children, possibly due to the increased fear of needles. 31 However, experienced paediatric anaesthesiologists know that children also fear a face mask.…”
Section: Discussionmentioning
confidence: 99%
“…18,22,30,31 Inhalational anaesthesia is thought to be more suitable for children, possibly due to the increased fear of needles. 31 However, experienced paediatric anaesthesiologists know that children also fear a face mask. 28,32 Children do not accept an unknown object on their face, and start manifesting their discontent immediately after the mask is placed there.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[4] Ketamine is also known as a dissociative anesthetic agent which has been used as an oral sedative for many years. [416–18] Promethazine is an antihistaminic used for mild sedation for daily dental patients. [15] To monitor the safety of the cases, such measurements are being tested with a 15-minute interval on recordings for both pulse oximeter and the BP.…”
Section: Discussionmentioning
confidence: 99%